2008
DOI: 10.1159/000135674
|View full text |Cite
|
Sign up to set email alerts
|

Hypomineralized Second Primary Molars: Prevalence Data in Dutch 5-Year-Olds

Abstract: The aim of this cross-sectional observational study was to report on the prevalence of hypomineralizations in second primary molars in 5-year-old Dutch children. In the study 386 (45% girls) 5-year-old Dutch children, all insured by a Health Insurance Fund, participated. Scoring criteria for molar incisor hypomineralization molars were adapted to score second primary molars. The prevalence of hypomineralized second primary molars (HSPM) was 4.9% at child level and 3.6% at tooth level. Most HSPMs (87%) showed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
137
6
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(175 citation statements)
references
References 18 publications
11
137
6
21
Order By: Relevance
“…[5] Elfrink et al [5] defined DMH as idiopathic hypomineralization of 1-4 s primary molars. DMH is also considered to be a predictive factor for MIH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Elfrink et al [5] defined DMH as idiopathic hypomineralization of 1-4 s primary molars. DMH is also considered to be a predictive factor for MIH.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Prevalence of DMH is reported to be 4.9-9%. [5,6] Etiology DDE can be described either as hypoplasia or hypomineralization. Disturbance in ameloblast functioning in the secretory stage of enamel formation results in enamel hypoplasia while disturbances in transitional and/or maturation stage may lead to hypomineralization defect, [7] of which MIH (and DMH) is a form.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that the teeth that are the most often affected by caries in the primary dentition are the second primary molars (Elfrink et al 2006(Elfrink et al , 2010. Hypomineralised molars frequently suffer posteruptive enamel breakdown and severe carious lesions (Elfrink et al 2008(Elfrink et al , 2010. Moreover, children with HSPM frequently display a more rapid progression of caries (Ghanim et al 2013), and the lesions become more severe as the children increase in age (Ghanim et al 2013).…”
mentioning
confidence: 99%
“…Uma possível consequência de um esmalte defeituoso, por exemplo, é um rápido desenvolvimento de lesões de cárie, logo após a erupção dos molares permanentes, com necessidade de procedimentos clínicos e tratamentos recorrentes. (10,11,12) Defeitos semelhantes aos da MIH, em segundos molares decíduos, estão sendo descritos na literatura (13,14), recebendo recentemente a nomenclatura de "Deciduous Molars Hypomineralization" (DMH), o que poderia ser traduzido como hipomineralização de molares decíduos. Esses defeitos estruturais levam a um aumento da sensibilidade devido à dentina exposta e/ou perda de elementos dentários muito precocemente, em um número significativo da população pediátrica.…”
Section: Introductionunclassified
“…A falta de acompanhamento médico durante a gestação mostrou porcentagem elevada, mas sem valor estatístico; dos indivíduos pesquisados que possuíam MIH (N=9), 22,22% informaram não ter feito pré-natal (p-valor 0,19; OR:3). Em relação a idade gestacional 11,11% das crianças com MIH eram prematuras (2)(3)(4)(5)(6)(7)(8)(9)14). Das crianças com MIH, 66,7% mamaram no seio materno mais do que 1 ano, (p-valor=0,05) (95% de confiança) mostrando uma relação estatisticamente significativa.…”
unclassified